L’ETHIQUE EN MATIERE DE SANTE ENTRE ANTINOMIES, LIBERTE DE CHOIX ET DIFFICULTE DU QUOTIDIEN - Cersosimo, Giuseppina (European Scientific Journal, ESJ, 2014)
The progressive increase of biotechnology, of more and more sophisticated and customized drugs, springs from a real requirement of citizens or instead from an offer coming from different corporations? Ethics in health care is everyday more contradictory, permeated by antinomies, freedom of choice, inequalities and problems connected to everyday life.